Electroreflectance imaging of gold–H3PO4 supercapacitors. Part I: experimental methodology. Issue 4 (28th January 2016) - Maize, Kerry; Kundu, Arpan; Xiong, Guoping; Saviers, Kimberly; Fisher, Timothy S.; Shakouri, Ali
Abstract : Electroreflectance microscopy is demonstrated as a high-resolution, non-contact method to image dynamic charge distribution in integrated microsupercapacitor structures during fast voltage cycling. Abstract : Electroreflectance microscopy is demonstrated as a high-resolution, non-contact method to image dynamic charge distribution in integrated microsupercapacitor structures during fast voltage cycling. Electroreflectance camera images of a gold electrode H3 PO4 polymer electrolyte microsupercapacitor reveal time varying charge distribution with submicron spatial resolution, millisecond time resolution, and electroreflectance resolution on the order of 500 nC cm −2 . A model describing changes in the metal electrode's optical constants as a function of free electron concentration shows good agreement with measured electroreflectance. The proposed method can be used for sensitive, non-contact measurements of charge spatial distribution, and defect and performance characterization in electrode–electrolyte microdevices.